Principles of Food Toxicology - Püssa, Tõnu (CRC Press, 2008)
Presents general and food-specific principles of toxicology with examples of food-related poisons and poisonings from around the world. This book explains the routes of absorption, metabolism, and elimination; toxic response; the determination of foreign substances; and the evaluation of toxicity and risk analysis.